PENGARUH DESAIN BUKAAN CAHAYA TERHADAP KENYAMANAN VISUAL DI WHEELS COFFEE ROASTERS RIAU BANDUNG - Kusnadi, Daniel; Dewi Pangestu, Mira (Jurnal Riset Arsitektur, 2025)
Abstract - Daylighting is one of the important aspects in architecture. Daylighting in cafes or restaurants can provide various benefits, including creating a comfortable and pleasant atmosphere for visitors and helping to reduce energy costs. However, excessive brightness can cause glare and become a problem that disrupts the comfort of customers and employees. Insufficient daylight can also affect visual comfort, making objects less clear and causing contrast between the workspace and the openings. Generally, natural light enters the room through side openings such as windows. However, natural light often struggles to penetrate the room due to nearby buildings or the bulky shape of the building, hence the use of overhead openings such as skylights. Wheels Coffee Roasters Riau Bandung is one of the cafes in the city of Bandung. Wheels Coffee Roaster has two indoor spaces with very different characteristics of daylighting. The first indoor space is the dining and bar area in the atrium, with top lighting in the form of a combination of skylights and clerestory. In addition to being a source of daylight, the skylight also serve as a distinctive feature of this cafe and support the micro-tropical concept used in its interior design. The second indoor space is the dining area adjacent to the atrium, which has two side openings, namely openings facing the atrium and the outside. The research conducted is descriptive-evaluative with a quantitative-qualitative approach. The research areas include the space below the atrium skylight, which serves as the dining and bar area, and the space adjacent to the atrium, which serves as the dining area. Simulation of sunlight movement on the building is used to determine the research time. In addition, simulations are used to collect data and evaluate the quantity and quality of existing natural lighting. Simulations are also used to optimize the study object. This research resulted in several conclusions. First, the visual comfort of the dining and ba area has not been achieved in terms of daylighting quality due to disruptive glare that is intolerable. Second, the visual comfort of the dining area adjacent to the atrium has not been achieved in terms of quantity and quality of daylighting because the illuminance does not meet the standards, and there is contrast when looking towards both side openings. Changing the type of translucent glass for the skylights and clear glass for the clerestory with a glass 50% significantly reduces glare in the dining and bar area in the atrium, although some glare still persists at certain times and is intolerable. Changing the shading elements and dimensions of the openings facing the outside can improve illuminance and reduce contrast ratios in the dining area adjacent to the atrium. Keywords: café, daylighting, visual comfort, opening design